Endothelial dysfunction and hemostatic imbalance in CAR T-cell-associated toxicities: pathophysiological insights and the role of circulating biomarkers - Moreno-Castaño, Ana Belén; Iraola, Gontzal; Martínez-Cibrián, Núria; Albiol, Nil; Prats, Daniel-Nicolás Marco; Martinez-Sanchez, Julia; Castro, Pedro; Diaz-Ricart, Maribel (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment of relapsed or refractory hematologic malignancies. While its clinical efficacy is well established, CAR T-cell therapy is frequently associated with severe immune-mediated toxicities, including cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), coagulopathy, and hemophagocytic lymphohistiocytosis-like syndrome (IEC-HS). Increasing evidence suggests that endothelial dysfunction, hemostatic imbalance, and complement activation are key contributors to the pathogenesis of these complications. Substantial research efforts have focused on identifying circulating biomarkers capable of predicting toxicity onset and severity, as well as stratifying patients at risk for early non-relapse mortality. In this review, we summarize the current understanding of the pathophysiological mechanisms underlying early CAR T cell–related toxicities, with particular emphasis on biomarkers of endotheliopathy and related pathways involved in their development. We focus on highlighting translational biomarkers with potential diagnostic, prognostic, and monitoring value that could be implemented in clinical practice to improve patient risk stratification, differential diagnosis, and therapeutic follow-up.